In vivo imaging flow cytometer - Alt, Clemens; Lee, Ho; Pitsillides, Costas (My University, 2007)
Purpose: An in vivo flow cytometer was developed recently, providing quantification of fluorescently labeled cells in live animals without extracting blood samples. This non-invasive procedure allows continuously tracking a cell population of interest over long periods of time to examine its dynamic changes in the circulation. However, it has not been shown that counting signals arise from individual cells. Furthermore, cell morphology and cell-cell interaction in the blood stream (e.g. aggregation) are not visualized. Here we describe an imaging in vivo flow cytometer. Material and Methods: Fluorescence images are obtained simultaneously with quantitative information on a DiD-labeled cell population. As fluorescent cells pass through the slit of light focused across a blood vessel, the excited fluorescence is detected confocally. This cell counting signal triggers a strobe beam and an intensified CCD camera to capture a snapshot image of the cell as it moves down-stream from the slit. Results: Nearly all peaks counted as circulating T-cells originate from individual cells, while cell aggregates were rarely observed (<2%). Counting signal amplitude variation is attributed to uneven dye-loading among cells. We identify non-T-cells by their abnormal shape and size. Cell velocity was measured by determining the traveled distance from the slit within the delay of the strobe pulse or by applying multiple strobe pulses during the integration time of the CCD camera. Conclusions: An improved in vivo imaging flow cytometer can be a useful tool for studying cell populations in circulation
Keywords: Flow cytometry; Cell aggregation; T cells; Blood; Blood-vessels